Increased basal oxidation of peroxiredoxin 2 and limited peroxiredoxin recycling in glucose-6-phosphate dehydrogenase-deficient erythrocytes from newborn infants - Cheah F.-C.; Peskin A.V.; Wong F.-L.; Ithnin A.; Othman A.; Winterbourn C.C. (FASEB, 2024)
Indexed by SCOPUS/WOS